Checklist of the Pacific marine macroalgae of Central America - Fernández García, Cindy (2011)
Our present knowledge of marine macroalgal diversity for the Central American Pacific coast is limited by the short history of investigations (ca. 100 years) and few algal spe- cialists through a large geographical area. While recent checklists have emerged for other regions of the eastern Pacific, there have been virtually no attempts to inventory macroalgal diversity for the Pacific of Central America. This checklist of the marine macroalgae was developed based on published scientific literature and unpublished records in stu- dent theses. A total of 379 species records are regarded as current valid names of marine macroalgae. The red algae (Rhodophyta) had the highest species number (252 species), followed by green algae (Chlorophyta: 81 species) and brown algae (Phaeophyceae: 46 species). The country with the greatest diversity of marine macroalgae is Costa Rica with 216 species, followed by Panama with 174, El Salvador with 146, Nicaragua with 24, and Guatemala with 16. At present, there are no published records for the Pacific coast of Honduras. Variation in number of species throughout the Pacific coast of Central America is likely due to differen- ces in geomorphology, habitat heterogeneity among national coastal-marine zones, and unbalanced research efforts.